ELECTROCHEMICAL DEPOSITION AND DISSOLUTION OF THALLIUM OXIDE (III) - SEILKHANOVA, Gulziya A.; KURBATOV, Andrey P.; USSIPBEKOVA, Yenlik Zh.; BEREZOVSKIY, Andrey V.; NAURYZBAEV, Michael K. (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The regularities of precipitation and dissolution of thallium (III) oxide were studied by using cyclic and linear voltammetry. It is established that at 1.5V potential, a peak corresponding to the process of oxidation of monovalent to trivalent thallium is observed, according to: Tl+ → Tl3+ + 2e-. Two peaks are observed in the cathode region, at 0.65V and -0.17V potential values. At E = -0.17V, the thallium oxide Tl2O3 dissolves, as at E = 0.65V, the intermediate products of the hydrolysis of trivalent thallium (Tl(OH)2+, Tl (OH)2+) are probably recovered. It was found that with increase of solution pH, the dissolution processes of thallium oxide intensified, while the optimum pH value was 11, also activation energy of the electrodeposition of thallium(III) oxide were calculated.